Robot-Assisted Diagnostic Laparoscopy: A Safe and Feasible Adjunct to the Management of Massive Spontaneous Pneumoperitoneum - Qingwen Kawaji; Sami Shoucair; Ali Darehzereshki; Alain Abdo (Case Reports in Surgery)
Pneumoperitoneum is the abnormal presence of free air in the peritoneal cavity. Oftentimes, it is a surgical emergency requiring exploratory laparotomy as most cases of pneumoperitoneum are due to perforated hollow viscus. However, not all pneumoperitoneum cases are surgical; nonsurgical pneumoperitoneum can arise from thoracic, abdominal, gynecologic, and other causes. We present a case of a 35-year-old male who developed a non-surgical pneumoperitoneum in the setting of drug overdose. The patient underwent robot-assisted diagnostic laparoscopy without findings of perforation or other pathology. Resolution of pneumoperitoneum was evidenced on follow-up computed tomography scan. This case emphasizes the importance of diagnostic laparoscopy in the setting of a confusing clinical picture and the feasibility of utilizing the robotic approach in hemodynamically stable patients.